A pregnant woman with primary hyperparathyroidism: a case report - Yorulmaz, Goknur; Kebapci, Nur; Onbasi, Kevser; Efe, Belgin; Akalin, Aysen (The European Research Journal, 2016)
Primary hyperparathyroidism is diagnosed with an increase of calcium levels and a decrease in phosphorus levels. Primary hyperparathyroidism is a rare condition in pregnancy. Calcium levels tend to be low in pregnant women, and high levels of calcium can point a primary hyperparathyroidism. Here, we report an original case of a pregnant woman with primary hyperparathyroidism who was fully healed after the surgery. A 30-year-old pregnant women (10th gestational week), admitted to the endocrinology department for management of thyrotoxicosis, when high calcium levels (11.8 mg/dL) were found in the laboratory tests. The parathyroid hormone level was 135 pg/ml. Ultrasound imaging revealed a parathyroid adenoma (12x7x27mm). She had maintained high calcium levels despite the medical treatment, for this reason, she had surgery in the second trimester. Our case was diagnosed early due to early recognition of calcium elevation. The mother and the foetus had not any complication. Pregnant women tend to have low calcium levels hence if a hypercalcemia situation appears in pregnant women; primary hyperparathroidism has to be suspected.